Al-Ghazali's Concept of Qolbu Education Thought and Its Relevance to the Character Education System in Indonesia - Munawaroh munawaroh; Saepudin; Sanin Sudrajat; Andriansyah (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
The thought of heart education according to Al-Ghazali is an approach that integrates spiritual and moral aspects in the educational process. Al-Ghazali emphasized that education does not only aim to develop intellectual aspects, but also to shape individual character and spirituality. In his view, the heart has an important role in decision-making and influencing individual behavior. The goal of education of the heart is to draw closer to Allah, achieve moral perfection, and produce useful knowledge. The proposed educational methods include learning through example, reflection, discussion, and spiritual practices. Al-Ghazali's thoughts on education of the heart are highly relevant in the context of contemporary education, especially in the development of character and individual integrity. The paper also discusses the purpose and implementation of the heart's thoughts in education.